The SUPERCOLD-CGM Survey. II. [C i](1–0) Emission and the Physical Conditions of Cold Gas in Enormous Lyα Nebulae at z ∼ 2 - Jianan Li; Bjorn H. C. Emonts; Zheng Cai; Jianrui Li; Ran Wang; Montserrat Villar-Martín; Fabrizio Arrigoni Battaia; Mingyu Li; Yunjing Wu; Ilsang Yoon; Matthew D. Lehnert; Kyle Massingill; et al. (The Astrophysical Journal)
We report Atacama Large Millimeter/submillimeter Array and Atacama Compact Array observations of atomic carbon ([C i ](1–0)) and dust continuum in 10 enormous Ly α nebulae hosting ultraluminous Type-I QSOs at z = 2.2–2.5, as part of the Survey of Protocluster ELANe Revealing CO/C i in the Ly α Detected CGM. We detect [C i ](1–0) and dust in all 10 QSOs and five companion galaxies. We find that the QSOs and companions have higher gas densities and more intense radiation fields than Luminous Infrared galaxies and high- z main sequence galaxies, with the highest values found in the QSOs. By comparing molecular gas masses derived from [C i ](1–0), CO(4−3), and dust continuum, we find that the QSOs and companions display a similar low CO conversion factor of α _CO ∼ 0.8 M _☉ ${[{\rm{K}}\,\mathrm{km}\,{{\rm{s}}}^{-1}\,{\mathrm{pc}}^{2}]}^{-1}$ . After tapering our data to low resolution, the [C i ](1–0) flux increases for nine QSOs, hinting at the possibility of [C i ](1–0) in the circumgalactic medium (CGM) on a scale of 16−40 kpc. However, the [C i ](1–0) sensitivity is too low to confirm this for individual targets, except for a tentative (2.7 σ ) CGM detection in Q0050+0051 with ${{M}}_{{{\rm{H}}}_{2}}$ = (1.0–2.8) × 10 ^10 M _☉ . The 3 σ mass limits of molecular CGM for the remaining QSO fields are (0.2–1.4) × 10 ^10 M _☉ . This translates into a baryon fraction of <0.4%–3% in the molecular CGM relative to the total baryonic halo mass. Our sample also includes a radio-detected active galactic nuclei, Q1416+2649, which shows [C i ](1–0) and CO(4−3) luminosities an order of magnitude fainter for its far-infrared luminosity than other QSOs in our sample, possibly due to a lower molecular gas mass.